Recent Advances in Direct Optical Patterning of Inorganic Materials and Devices - Baek, Seongheon; Son, Jae Sung (Advanced Physics Research, 2024)
Direct patterning technology holds significant promise owing to its ability to streamline complex patterning processes, fostering affordable design and production of various devices. Direct optical lithographic techniques have recently been applied to diverse ranges of functional inorganic nanomaterials, providing a viable alternative to conventional photolithography. These techniques facilitate the fabrication of diverse thin‐film devices and enable 3D printability for inorganic microarchitectures. This review discusses the recent progress in the direct patterning of inorganic materials and associated device fabrication. The chemical design of inorganic building blocks is delved into, which entails the photochemistry of surface ligands or additives that respond to external stimuli and the different patterning methodologies predicated on these external stimuli. Moreover, device fabrication is introduced through direct patterning methods, highlighting examples from optoelectronic, electronic, and energy devices. Last, the prospects of this field are presented, focusing on materials and processes. Direct patterning technology for inorganics attract tremendous attention due to its potential of simple and cost‐effective manufacturing of various devices. In this review, the recent progress in direct optical patterning methods for inorganic nanomaterials is presented. The fundamental solidifying mechanism, various methodologies, and associated device fabrication, is discussed highlighting several monumental studies in this field.